Open-label Phase II study of everolimus plus endocrine therapy in postmenopausal women with ER-positive and HER2-negative metastatic breast cancer (Chloe trial) - Shimoi T; Shimomura A; Shien T; Uemura Y; Kato H; Kitada M; Toyama T; Aihara T; Mukai H (Open Access Journal of Clinical Trials, 2018)
Tatsunori Shimoi,1 Akihiko Shimomura,1 Tadahiko Shien,2 Yukari Uemura,3 Hiroaki Kato,4 Masahiro Kitada,5 Tatsuya Toyama,6 Tomohiko Aihara,7 Hirofumi Mukai8 1Department of Breast and Medical Oncology, National Cancer Center Hospital, Tokyo, Japan; 2Department of Breast and Endocrine Surgery, Okayama University Hospital, Okayama, Japan; 3Division of Biostatistics, Clinical Research Support Center, Tokyo University Hospital, Tokyo, Japan; 4Department of Thoracic Surgery, Teine Keijinkai Hospital, Sapporo, Japan; 5Department of Surgery, Asahikawa Medical University, Asahikawa, Japan; 6Department of Oncology, Immunology and Surgery, Nagoya City University, Graduate School of Medical Science, Nagoya, Japan; 7Department of Breast Surgery, Keimeikai-Aihara Hospital, Osaka, Japan; 8Department of Breast and Medical Oncology, National Cancer Center Hospital East, Chiba, Japan Background: This is a randomized, multicenter, open-label, Phase II study designed to evaluate the efficacy of everolimus added to continuous aromatase inhibitor (AI) administration in patients who had maintained stable disease or a better response for at least 5 months.Patients and methods: Patients will be randomized to everolimus and standard therapy groups (1:1 ratio). In the everolimus group, patients will receive everolimus in addition to the AI agent. The standard therapy group will continue AI alone treatment. The primary endpoint is progression-free survival. Target accrual is 130 patients with a two-sided type I error rate of 10% and 80% power to detect 35% risk reduction.Conclusion: The Chloe trial will provide important information about the efﬁcacy and safety of adding everolimus to AI in patients with estrogen receptor-positive and human epidermal growth factor 2-negative metastatic breast cancer. Keywords: hormone receptor-positive, breast cancer, aromatase inhibitor, everolimus